Antibacterial Activity Test of Arabic Coffee Leaf Extract (Coffea arabica L.) Against The Bacteri Aeromonas hydrophila - Nugraha, Nabilla Argadia; Puteri, Prianti Nurmeilia; Destiana, Anggari Linda; Wahyuni, Fitra (Jurnal Biologi Tropis, 2025)
Arabica coffee leaves (Coffea arabica L.) contain compounds known as secondary metabolites that have antibacterial properties, capable of suppressing the growth of Aeromonas hydrophila bacteria. The purpose of this study was to identify phytochemical compounds contained in Arabica coffee leaves (Coffea arabica L.), evaluate the antibacterial effectiveness of these leaves against Aeromonas hydrophila bacteria, and determine the concentration of Arabica coffee leaf extract that is most effective in inhibiting the growth of these bacteria. The method used in this research is the disc diffusion method. The concentrations of Arabica coffee leaf extract used were 25%, 35%, and 45%, and the data were analyzed using Kruskal Wallis test and Dunn's post hoc test. The results showed that the ethanol extract of Arabica coffee leaves had antibacterial activity. At a concentration of 45%, the extract showed an average inhibition zone of 15.95 mm against Aeromonas hydrophila, which is categorized as a very strong inhibition level. The Kruskal Wallis test yielded a significance level of 0.001 (p < 0.005), indicating a significant difference.